The Effect of potassium dosage on selected growth parameters and yield response modeling on potatoes grown in Molo, Kenya - Maingi, Francis M.; Mbuvi, Harun M. (Journal of Scientific Agriculture, 2020)
Abstract: The Molo region of Kenya has experienced decreased potato acreage yields over the years. This has impacted negatively economic endeavors and food security of the region and Kenya at large. A preliminary study on the physical-chemical characterization of the soils indicated that they were deficient in the amount of available potassium. This finding was very important because the majority of the farmers in the region replenish phosphorous and nitrogen but not potassium. Subsequently, the present study was undertaken to determine the effect of replenishing selected farm soils with various potassium levels on the growth and productivity of ‘Shangi’ a variety grown in Molo Sub-county and ultimately determine the soil optimum potassium dose requirement. A field experiment was conducted with seven model-based K fertilizer treatments (0, 33.3, 41.5, 55.3, 133.3, 200 and 266.7 kg K2O/ha) and three replications in Randomized Complete Block Design (RCBD). The potassium sorption study was conducted using soil samples as adsorbent while varying the K+ concentration in solution. The data obtained were treated using both linearized and non-linearized Freundlich adsorption isotherms. The optimum potassium fertilizer rate was evaluated using yield response models (Quadratic, linear-plateau, quadratic-plateau, and square root). The results of the study showed that the increase in soil potassium levels led to a significant increase in growth and yield parameters. Aerial stem number, leaf number per plant, and plant height recorded increase with an increase in K levels. The sorption data were found to fit best in linearized Freundlich isotherm based on correlation coefficient values (R2) and error function analysis. The potassium buffering capacity ranged from 13.667-46.068 with a mean of 33.6 ± 17.4mg/Kg. The quadratic model fitted the data better than other models with R2 (0.9559) and SSE (18.237). K2O fertilizer application at 200 Kg/ha maximized the potato tuber yield to 30.111 Ton/ha. The result showed clearly that there is a need to adopt the use of potassium-based fertilizer according to soil requirements in this region to realize good tuber yield.